The Use of Bekai (Pycnarrhena tumefacta Miers) as Biovetsin and Medicine by the Dayak Tribe in Setarap Village, Malinau, North Kalimantan - Suciyati, Alfi; Putri, Devi Enjeliana; Marshella, Mega (Biopedagogia, 2024)
Bekai (Pycnarrhena tumefacta Miers) is one of the plants used by the Dayak Tribe in Setarap Village, Malinau Regency as a natural flavouring (bio-vetsin) and as a medicinal plant. Research on the use of Bekai plants by the Dayak Tribe in Kalimantan is still very limited. This study aims to determine how the Bekai plant is used by the Dayak Tribe, especially as a bio-vetsin and medicinal plant. The research method used is an ethnobotanical study with a qualitative descriptive method. Primary data were obtained through direct observation and interviews in the field, secondary data were obtained through a literature review. The results of this study are that the use of Bekai as a bio-vetsin: (a) young leaves are crushed or pounded with vegetables to be cooked, and (b) old leaves are mixed directly into the cooking. Bekai plants are also used by the Dayak Tribe in Setarap Village as a treatment for various types of diseases. How to use it is by boiling the leaves (for cancer treatment, aches and pains, post-operative healing, fever, headaches), and brewing the fruit (for mouth ulcers and sore throats).